BRILLIANT BLUE G-ASSISTED INTERNAL LIMITING MEMBRANE PEELING FOR MACULAR HOLE: A Systematic Review of Literature and Meta-Analysis. Issue 5 (May 2016) - Azuma, Kunihiro; Noda, Yasuo; Hirasawa, Kazunori; Ueta, Takashi
Abstract : Purpose: To evaluate the effect of internal limiting membrane peeling with brilliant blue G (BBG) for the treatment of macular hole compared with peeling procedures with other dyes or without dye. Methods: MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) were systematically reviewed. Outcome measures were the primary closure rate and postoperative best-corrected visual acuity. Results: Nine studies that included 846 eyes were selected. There was no significant difference in preoperative best-corrected visual acuity between the BBG and no BBG (i.e., other dyes or no dye) groups (mean difference −0.02 logMAR [equivalent to 1 Early Treatment Diabetic Retinopathy Study (ETDRS) letter]; 95% confidence interval −0.09 to 0.04 [−2–4.5 ETDRS letters]; P = 0.45). The macular hole closure rate using BBG was not significantly different from that using indocyanine green (odds ratio 1.98; 95% confidence interval 0.71–5.48; P = 0.19). The postoperative best-corrected visual acuity was more favorable with BBG than with indocyanine green (mean difference −0.10 logMAR [5 ETDRS letters]; 95% confidence interval −0.16 to −0.03 [1.5–8 ETDRS letters]; P = 0.004) or with no BBG (mean difference −0.11 [5.5 ETDRS letters]; 95% confidence interval −0.18 to −0.04 [2–9 ETDRS letters]; P = 0.003). Conclusion: BBG could contribute to better visual acuity outcome than other dyes for internal limiting membrane peeling in patients with macular hole; however, it does not significantly influence the closure rate. Abstract : Systematic review and meta-analysis of current literature suggest that compared with other dyes, brilliant blue G-assisted peeling of the internal limiting membrane could lead to better postoperative visual acuity while it does not influence the primary closure rate in patients with macular hole.